Penerapan Unsur-Unsur Arsitektur Neo-Vernakular Pada Perancangan Galeri Seni Budaya Melayu Riau Di Pekanbaru - Dyos Pangendra; Wahyu Hidayat; Mira Dharma Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The diversity of Malay culture in Riau Province becomes one of the things that must be preserved and developed in order to stay well preserved. Riau can be the center of Malay culture in Indonesia with its diverse cultural assets. Therefore, it is necessary to have a to appreciate and preserve Malay culture in order to maintain by providing facilitation of Malay Art Gallery in Pekanbaru. Art Gallery of Riau Malay Culture is designed to represent elements of Riau Malay culture on its design. The purpose of this research is to design the Malay Cultural Art Gallery of Riau by applying the elements of Neo-Vernacular Architecture and developed in a more modern form. In the design of Riau Malay Art Art Gallery, there are three main functions, namely manager-supporting, gallery, and amphitheater which of these three functions apply the elements of Neo-vernacular Architecture. this theme can be the basic reference in the design as well as the unique value that colored the overall design result. This approach will produce a modern form but still have local cultural values. the concept is "Ark of Lancang Kuning" which is an icon of Riau Malay culture. There are two main buildings namely the manager and the gallery. Building managers more emphasis on the concept and building the gallery more to the theme of the theme. Overall the building characterizes predefined themes and concepts.The combination of themes and concepts that will produce a modern form but still apply the value of local culture.Keywords: Riau Cultural Malay Art, Neo-Vernacular Architecture, Pekanbaru